The Evolution of Thai Folklore and Oral Traditions: Preserving Narratives in a Modernized Society - สะสอง สัญญา (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2024)
This paper examines the evolution of Thai folklore and oral traditions, focusing on the impact of modernization on the preservation of cultural narratives. Thai folklore, encompassing myths, legends, and moral tales, serves as a vital repository of cultural identity, expressing the values, beliefs, and historical experiences of Thai communities. As modernization advances, traditional narratives face challenges due to the influence of technology, globalization, and shifts in audience engagement. Younger generations, influenced by digital media, are gradually moving away from traditional storytelling, raising concerns about cultural continuity. However, modernization also offers opportunities for revitalizing these traditions. Digital platforms, educational integration, and community initiatives provide new pathways for documenting and sharing folklore, ensuring its relevance and accessibility in contemporary society. By analyzing how Thai folklore adapts to changing contexts, this research underscores the resilience of cultural narratives and highlights the importance of safeguarding intangible heritage. The findings suggest that a balanced approach, combining preservation and adaptation, is essential for maintaining the cultural significance of Thai folklore amidst modern influences.